Analysis and Design of “Universitas Dinamika” Web Page Design in Creating Customer Experience and Buying Interest of New Students from Sidoarjo - Gerdy Irfandy; Ayouvi Poerna Wardhanie; Candraningrat Candraningrat (Jurnal Bisnis dan Keuangan, 2022)
The community's need for higher education in Indonesia continues to grow, seen from the increasing number of higher education institutions every year. Dinamika University as one of 328 Private Universities (PU) in East Java has implemented marketing tools using a website ( www.dinamika.ac.id ). However, the availability of the website has not been proven to be effective in attracting new students to register at Dinamika University. From 5134 new students, 3785 students (74%) received admissions information through offline media, 1256 students (24%) through online media, and 93 students (2%) through other media. This study aims to determine the effect of the design of visual and verbal web page elements on the buying interest of new students through customer experience. This study combines the PLS-SEM as an analytical method and the Double Diamond method in designing web page recommendations using Warp PLS 7.0 and Adobe XD. 100 experimental respondents were obtained from the purposive sampling method. In the process of designing web page recommendations, the crazy 8 design method will be used to sketch design, supervoting to select design recommendations, and usability testing to test prototypes. The results of this study prove that there is a significant influence between visual web page design on customer experience, verbal web page design on customer experience, verbal web page design on buying interest, customer experience on buying interest, visual web page design on buying interest through customer experience. However, there is also an insignificant effect between visual web page design on buying interest, verbal web page design on buying interest through customer experience. The results of testing the prototype obtained an average score of "Very Good" in its usefulness value.